Phytoliths indicate significant arboreal cover at Sahelanthropus type locality TM266 in northern Chad and a decrease in later sites. Issue 106 (May 2017) - Novello, Alice; Barboni, Doris; Sylvestre, Florence; Lebatard, Anne-Elisabeth; Paillès, Christine; Bourlès, Didier L.; Likius, Andossa; Mackaye, Hassane Taisso; Vignaud, Patrick; Brunet, Michel
Abstract: We analyzed phytolith and diatom remains preserved at 45 Miocene and Pliocene localities dated between 8 and 1 Ma in northern Chad (16–17°N). Some of these localities yielded cranial remains, lower jaws, and teeth of the hominin species Australopithecus bahrelghazali (∼3.6 Ma) and Sahelanthropus tchadensis (∼7 Ma). Of the 111 sediment samples analyzed, 41 yielded phytoliths, 20 yielded diatoms, and seven yielded both phytoliths and diatoms. Freshwater planktonic and tychoplanktonic diatom species, indicative of lacustrine conditions, are dominant (>91%) in the samples. The phytolith assemblages indicate an opening of the vegetation and a general trend toward an expansion of grass-dominated environments during the time spanning the two hominin occurrences in Chad. The phytoliths suggest the presence of a mosaic environment, including closed forest patches, palm groves, and mixed/grassland formations, between 7.5 and 7 Ma, the replacement by palm grove-like vegetation at approximately 6.5–5 Ma, and the presence of exclusive grass-dominated formations after 4.5 Ma. The type-locality of S. tchadensis (TM266) was likely similar to modern palm grove formations with an arboreal cover percentage ≥40%. The type locality of A. bahrelghazali (KT12) was a grass-dominated ecosystem (likely savanna) with an unrated percentage of arboreal cover. Furthermore, the grass phytolith data support the existence of a (recurrent) Sahelian-like dry climate in northern Chad since at least 8 Ma. Therefore the local closed vegetation formations in the Djurab region at 7.5–7 Ma were sustained by aquatic systems (such as lakes or related rivers, marshes) rather than by extensive annual precipitation.